Academic language-related challenges at an English-medium university. Issue 49 (January 2021) - Kamaşak, Rifat; Sahan, Kari; Rose, Heath
Abstract: The study reported in this article investigated the linguistic challenges that students face at an English medium instruction (EMI) university in Turkey. The aims of the study were (1) to describe the challenges that students experience in their EMI classes; (2) to investigate how these challenges vary according to individual student characteristics; and (3) to validate a research instrument designed to explore academic language-related challenges in EMI contexts. Data were collected from undergraduate students (N = 498) using an online questionnaire, which had a structure based on challenges with respect to reading, writing, speaking, and listening. The analysis revealed that students found writing and speaking to be the most challenging areas in their EMI classes. The study also found significant differences in the challenges reported by students with respect to academic discipline, L1 background, prior EMI experience, and the type of exam taken to meet the university's language proficiency requirements. Implications are discussed with respect to EAP support for students and L2 proficiency entry requirements for EMI programs.